(untitled) (Research, Society and Development, 2022)
Gemological minerals, also known by the popular term of precious stones, for their characteristics of color and shine, promote the attention of many collectors and stimulate the jewelry trade around the world, with the state of Minas Gerais as an interest in several aspects. This work focuses on municipalities in the micro-region of Itabira that has a strong history of production of these minerals. The production of emerald and several other substances from each municipality in the micro-region was analyzed through data collection available in the database of the Mining Registation maintained by the National Mining Agency - ANM, considering the processes with active status. The mineral diversity for the cities considered is significant. We were able to observe the historical production mark, the current phases of the projects, main occurrences of gemological minerals and a general panorama, as examples of the results achieved with this research.